The Effect Of Budgetary Participation, Organizational Commitment And Budget Goal Clarity On Managerial Performance With Internal Control As Moderating Variable (Survey On Individual Office Holders At Rsud Prof. Dr. Margono Soekarjo In Purwokerto) - Yuniati Suryaningsih (EBBANK, 2013)
The aims of research are to analyze the significant effect of budgetary participation, organizational commitment as well as budget goal clarity on managerial performance and to analyze the effect of internal control in moderating on the causal relationship between budgetary participation, organizational commitment as well as budget goal clarity and managerial performance. This research was conducted at working area of RSUD Prof. Dr. Margono Soekarjo in Purwokerto. The amounts of respondents used in this research of 61 managerial, sampling technique used in this research is probability sampling (selected sample), whereas determination of amount of sample used the Slovin formula. To test the first, second and third hypotheses, it has used multiple linear regression analysis, then to test the fourth, fifth and sixth hypotheses, it has used moderated regression analysis. Based on the result of multiple linear regression analysis, it has got the t-statistic value of budgetary participation, organizational commitment as well as budget goal clarity each was greater than the value of t table, therefore the first, second and third hypotheses was accepted. The results of moderated regression analysis shows the t-statistic value of moderating_1 as well as moderating_2 variable each was smaller than value of t table, while the t-statistic value of moderating_3 variable was greater than value of t table, therefore the fourth and fifth hypotheses were rejected, whereas the sixth hypothesis was accepted. Based on the result of data analysis, it could be concluded that budgetary participation, organizational commitment as well as budget goal clarity has positive and significance effect on managerial performance, internal control has no significance moderate on the causal relationship between budgetary participation as well as organizational commitment and managerial performance, and internal control has significance moderates on the causal relationship between budget goal clarity and managerial performance. Based on the conclusions, it could be implied that in order to continuously improve the managerial performance, the RSUD Prof. Dr. Margono Soekarjo in Purwokerto needs to pay attention on the budgetary participation, organizational commitment and budget goal clarity policy. The way to do them were provide ample opportunities to the managerial to take an active role in formulating the budget, to meet the various needs and desires of the managerial tasks associated with the field of work or their responsibility area and to implement the budgeting system that clear, measurable and applicable